LEAP: A randomized–controlled trial of a lay-educator inpatient asthma education program. Issue 12 (December 2015) - Rice, Jessica L.; Matlack, Kristen M.; Simmons, Marsha D.; Steinfeld, Jonathan; Laws, Margaret A.; Dovey, Mark E.; Cohen, Robyn T.
Highlights: We evaluated an asthma education program based on Social Cognitive Theory. The lay-educator program was associated with improved asthma management behaviors. Utilizing volunteers as educators was inexpensive and sustainable. The program has widespread implications as an asthma education model. Abstract: Objective: To evaluate the impact of LEAP, a volunteer-based, inpatient asthma education program for families of inner-city children with asthma. Methods: 711 children ages 2–17 years admitted with status asthmaticus were randomized to receive usual care or usual care plus a supplemental education intervention. Both groups completed a baseline interview. Trained volunteer lay educators conducted individualized bedside education with the intervention group. Primary outcome was attendance at a post-hospitalization follow-up visit 7–10 days after discharge. Secondary outcomes included parent-reported asthma management behaviors, symptoms, and self-efficacy scores from a one month follow-up interview. Results: Post-hospitalization asthma clinic attendance was poor (38%), with no difference between groups. Families randomized to the intervention group were more likely to report use of a controller (OR 2.4, 95% CI 1.3–4.2, p < 0.01) and a valved-holding chamber (OR 2.9, 95% CI 1.1–7.4, p = 0.03), and were more likely to have an asthma action plan at follow up (OR 2.0, 95% CI 1.3–3.0, p < 0.01). Asthma self-efficacy scores were significantly improved among those who received the intervention ( p = 0.04). Conclusions: Inpatient asthma education by trained lay volunteers was associated with improved asthma management behaviors. Practice Implications: This novel volunteer-based program could have widespread implications as a sustainable model for asthma education.